Analysis of transient multiexponential signals using cepstral deconvolution - Abdussamad , U. Jibia; Salami, Momoh Jimoh Emiyoka; Khalifa, Othman Omran; Aibinu, Abiodun Musa (Elsevier, 2010)
We propose and test a new method of multiexponential transient signal analysis. The method based on cepstral deconvolution is fast and computationally inexpensive. The multiexponential signal is initially converted to a deconvolution model using Gardners' transformation after which the proposed method is used to deconvolve the data. Simulation and experimental results indicate that this method is good for determining the number of components but performs poorly in accurately estimating the decay rates. Influence of noise is not considered in this paper.